2022
DOI: 10.1038/s43856-022-00079-7
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise improves episodic memory in late adulthood: a systematic review and meta-analysis

Abstract: Background Aerobic exercise remains one of the most promising approaches for enhancing cognitive function in late adulthood, yet its potential positive effects on episodic memory remain poorly understood and a matter of intense debate. Prior meta-analyses have reported minimal improvements in episodic memory following aerobic exercise but have been limited by restrictive inclusion criteria and infrequent examination of exercise parameters. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 86 publications
1
28
0
Order By: Relevance
“…Among those that assessed it, 7 found evidence of publication bias (7 9,2022,24,26,32 out of 14) and, among them, only 3 adjusted the final effect (3 9,20,32 out of 7). Notably, one of the meta-analyses concluded benefits in episodic memory with physical exercise even after the publication-bias correction methods indicated a non-significant effect 32 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those that assessed it, 7 found evidence of publication bias (7 9,2022,24,26,32 out of 14) and, among them, only 3 adjusted the final effect (3 9,20,32 out of 7). Notably, one of the meta-analyses concluded benefits in episodic memory with physical exercise even after the publication-bias correction methods indicated a non-significant effect 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four meta-analyses 12,7,13,14,8,[15][16][17][18][19][20][21][22]9,[23][24][25][26][27][28][29][30][31][32] meeting the inclusion criteria were selected among the 2,000 records retrieved in the search (see Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis comprising of 28 studies (2156 participants) conducted by Zhidong and his team found that physical exercise could improve working memory in older individuals [ 220 ]. Aghjayan et al also conducted a meta-analysis investigating the effects of physical activities in older adults and found that aerobic exercises positively affect episodic memory as well [ 221 ]. Similarly, the same effects can also be observed in elderly patients with AD, with Jia et al reporting that physical activities contribute to their improvement in cognitive functions [ 222 ].…”
Section: Behavioral Effects Of Ee and Its Potential Application In Hu...mentioning
confidence: 99%
“…Mixed-effects analyses demonstrated the positive effect on episodic memory among studies with a high percentage of females (65–100%) and participants with normal cognition. Subgroup analyses revealed the moderating effect of age ( p = 0.027), particularly studies on participants with a mean age between 55 and 68 years, as opposed to 69–85 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%